INTERNALISASI PENDIDIKAN KARAKTER MELALUI PENDIDIKAN AGAMA KRISTEN - Ipiana; Kezia Dwi Novitasari; Yonathan Yakub Mononimbar (Sekolah Tinggi Teologi Duta Panisal, 2022)
Provide an understanding of character education to students so that an understanding of character education can be understood by students, and can be applied in the lives of students. through the internalization of character education and Christian religious education, with descriptive qualitative methods the researchers analyzed with literature studies to provide an important understanding of the internalization of character education through Christian religious education, exemplary and guiding attitudes, to provide effective understanding to students regarding character values to students so that the character of students increa